PENYIDIKAN TINDAK PIDANA PEMBALAKAN LIAR OLEH KEPOLISIAN RESOR BENGKALIS BERDASARKAN UNDANG-UNDANG NOMOR 18 TAHUN 2013 TENTANG PENCEGAHAN DAN PEMBERANTASAN PERUSAKAN HUTAN DI KABUPATEN BENGKALIS - FEBRI ARTISYAH; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
One of the actions that occur forest destruction is illegal. illegal logging are all activities of utilization of timber forest products illegally organized. This act is also an offense against the wild hukum.Logging has resulted in uncontrolled forest destruction. Increasing demand for wood to make people do illegal logging and timber from illegal logging is sold to companies that require the wood industry.The purpose of the study is to examine the investigation of criminal illegal logging by Police Bengkalis based on Law Number 18 Year 2013 concerning the Prevention and Eradication of forest destruction in Bengkalis, barriers Police Bengkalis in the criminal investigation illegal logging,attempt what are the do to overcome obstacles in the criminal investigation illegal logging.From this study can be concluded that the process of investigation of criminal illegal logging by Police Bengkalis based on Law Number 18 Year 2013 concerning the Prevention and Eradication of forest destruction in Bengkalis not run properly and as it should be. This is evidenced by too few criminal cases of illegal logging were able revealed by Police Bengkalis. obstacle that occur in the process of criminal investigation of illegal logging in Bengkalis Police is still a lack of quality human resources, still lack Bengkalis Police officers educated or graduate a Bachelor of Law, Police Investigator limited personnel and area, lack of facilities and amenities, Less coordination with the Department of Forestry. efforts that can be done to address the causes of the slow process of investigation criminal illegal logging by Police Bengkalis ie by Improving professional and high integrity of law enforcement officers, Holding learning activity for members of Police Bengkalis, Increase the number of personnel Investigator Police, improve facilities and existing facilities, improving coordination with the Department of Forestry. Suggestions Author,First Police Bengkalis should continue to improve its performance in dealing with any cases, Should Police Bengkalis take actions explicitly every criminal act illegal logging so that the investigation can run as expected,Should Police Bengkalis able to optimally developing partnerships with various potentials and and community members to proactively prevent crime that may be incurred as well in the disclosure of a case.Keywords: investigation-criminal act-illegal logging